Clams from Tagus estuary : microbiological, physiological and chemical responses to depuration, transpot and environmental stress - Anacleto, Patrícia Sofia Laranjeira, 1982- (2015)
Tese de doutoramento, Biologia (Biologia Marinha e Aquacultuta), Universidade de Lisboa, Faculdade de Ciências, 2014